y= 3x + 1

y= 2x – 3

When using the method called substitution, the y coordinate of the solution to the system of equations shown above is:

A. 13

B. -13

C. 11

D. -11

y= 3x + 1

y= 2x – 3

When using the method called substitution, the y coordinate of the solution to the system of equations shown above is:

A. 13

B. -13

C. 11

D. -11

Answer:Step-by-step explanation:The answer is D. -11

-3x+1=2x-3 (solve and you will get x= -4)

Substitute x in one of the equations to solve for x

y= 3(-4) + 1

y= -11